Unijna polityka strukturalna 2000-2006 i jej reforma - Bernaś, Bogumił; Kowalik, Paweł (Structural Policy of the European Union in 2000-2006 and its Reform, 2006)
The structural funds are of key importance to the member states in helping them strengthen their competitiveness. The enlargement of the Union to 25 member states and subsequently to 27 or more will make new problems. The European Union undertook a decision (in 2001) to reform a cohesion I policy for the period beginning in 2007. This article presents a structural policy in the period 2000- J -2006 and proposals for its reforms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 65-74